A Systematic Review of RCTs and quasi-RCTs on Traditional Chinese Patent Medicines for Treatment of Chronic Hepatitis B - 湛韬 魏星 陈泽奇 王东生 戴幸平 (Journal of Traditional Chinese Medicine, 2011)
Traditional Chinese patent medicines （TCPMs） are widely used for treatment of chronic hepatitis B （CHB） in China. To estimate the overall effectiveness of TCPMs for CHB, we performed a systematic review of clinical reports designed as randomized controlled trials （RCTs）. One hundred and thirty-eight available RCTs and quasi-RCTs on 62 TCPMs, involving 16,393 patients, were included. The methodological quality of these trials was generally ＂poor＂. Few trials （6.52%） reported the methods of randomization correctly. Another common problem was the lack of allocation concealment, proper blinding, and the reporting of lost cases and dropouts. Forty-two trials （30.43%） on 27 TCPMs reported some anti-viral effect of TCPMs. Others reported beneficial aspects, including improvements of liver function （79.71% of the studies）, liver fibrosis （29.99%）, and CHB symptoms （92.75%）. Forty-one articles （29.71%） reported mild adverse events with TCPMs but these occurred infrequently. In summary, the outcome of the report on currently registered TCPMs may be biased due to poor methodology. The data from these trials, therefore, is too weak to use in forming a recommendation for treatment of CHB. Nevertheless, five drugs （Dan Shen agents, Da Huang Zhe Chong pill/capsule, Shuang Hu Qing Gan granule, Fu Zheng Hua Yu granule and Cao Xian Yi Gan capsule） appear to be more effective than the other TCPMs.